Mesoporous hydrochar from Acacia falcata leaves by hydrothermal process for hexavalent chromium adsorption - Rajesh Juturu; Ramesh Vinayagam; Gokulakrishnan Murugesan; Raja Selvaraj (Scientific Reports)
Abstract This study evaluates mesoporous-hydrochar derived from Acacia falcata leaves via a single-step hydrothermal treatment for Cr(VI) adsorption. Material characterization indicated that the adsorbent has a rough and porous structure. FTIR analysis confirmed Cr(VI) adsorption through functional group interactions, evidenced by peak intensity changes and the emergence of a Cr–O bond vibration at 669 cm-1. Two new peaks were observed in XPS spectra, corresponding to Cr 2p at 577.04 eV (Cr 2p3/2) and 586.67 eV (Cr 2p1/2) after adsorption, further substantiating the adsorption and Cr(VI) reduction. Batch experiments showed an improved adsorption capacity of 30.47 mg/g. Kinetic investigation adhered to the pseudo-second-order model, whereas the equilibrium dataset satisfied the Freundlich model, indicating a heterogeneous adsorption mechanism involving physisorption and chemisorption. The thermodynamic evaluation confirmed spontaneous and endothermic adsorption. Regeneration studies showed reduced Cr(VI) removal performance after four cycles, attributed to pore blockage and loss of functional groups while maintaining effective reuse potential. Spiked studies in various water matrices showed a slight decrease in Cr(VI) removal efficiency, yet it maintained over 95% efficiency, demonstrating its potential for real-world water treatment applications.